PENGARUH KUALITAS PRODUK,CITRA MEREK,DAN E-WOM TERHADAP MINAT BELI ULANG LIPCREAM HANASUI (STUDI KASUS PADA KONSUMEN DI SOLO RAYA) - Dea ayu pramesti; Budi istiyanto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Beauty is one of the keys for women, it is no longer a woman's desire but a woman's need. Due to this, the level of the cosmetics industry in the world has soared, especially in Indonesia. Many cosmetic brands are competing to market their products and none other than Hanasui, Hanasui is a product from Indonesia which was produced by PT Eka Jaya Internasional from 2016, Hanasui is a brand of beauty products in Indonesian industry which has various brand innovations, one of which is Lipcream Hanasui, Lipcream Hanasui is a halal and BPOM-certified product with high quality and safe for the lips. This research was conducted to determine product quality, brand image, and e-wom influencing interest in repurchasing Lipcream Hanasui products. The population is consumers of Lipcream Hanasui products. The method used for sampling was non-probability sampling using purposive sampling techniques. A sample of 95 respondents who had purchased Hanasui Lipcream products in Solo Raya. This research was carried out using quantitative methods by collecting data using a questionnaire in the form of a Google form. Data instrument testing, classical assumption testing, and multiple linear regression analysis with the SPSS program are the techniques used to analyze the data. The results show that product quality,brand image,e-wom have a significant effect on repurchase interest in Lipcream Hanasui.